2013
DOI: 10.1007/s00701-013-1747-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of VKORC1-1639G>A polymorphism with susceptibility to ossification of the posterior longitudinal ligament of the spine: a Korean study

Abstract: Our results suggest that the VKORC1-1639G>A SNP may increase susceptibility to OPLL in women. However, there was only a statistical association in the female group despite a number of stratified analyses. Therefore, the findings should be interpreted with caution, and further genetic study is needed to improve our understanding of the role of VKORC1 polymorphisms in determining the risk of OPLL occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Beside non-genetic factors like mechanical stress, nutrition, glucose intolerance, and high body mass index, recent studies showed numerous genes are associated with the disease. Most of these genes are vital to the ossification process like NPPS, COL11A2, COL6A1, BMP2, BMP4, TGF-β1, TGF-β3 4 5 6 7 22 24 , and often aberrant expression of these genes can cause the pathological heterogeneous ossification 25 26 . This means a certain disorder in the upstream regulatory network of these critical factors may exists during the pathological process of OPLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside non-genetic factors like mechanical stress, nutrition, glucose intolerance, and high body mass index, recent studies showed numerous genes are associated with the disease. Most of these genes are vital to the ossification process like NPPS, COL11A2, COL6A1, BMP2, BMP4, TGF-β1, TGF-β3 4 5 6 7 22 24 , and often aberrant expression of these genes can cause the pathological heterogeneous ossification 25 26 . This means a certain disorder in the upstream regulatory network of these critical factors may exists during the pathological process of OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…The ossified ligaments formed osteophytes that gradually increases in size, which in turns causes compression of spinal cord and may lead to neurologic symptoms or severe neurologic deficit. Recent studies have shown that single nucleotide polymorphisms (SNPs) and gene expression variations in various genes are associated with OPLL development 3 4 5 6 7 , which implies genetic factors may play key roles in this process. However, the exact pathogenesis of OPLL still remains unclear, not to mention the underlying mechanism and its regulatory network.…”
mentioning
confidence: 99%
“…There are many genes reported to be associated with OPLL in human, including ENPP1 [24, 29], collagen 6A1 [27], transforming growth factor-β (TGFB) -1 [20], TGFB-3 [30], collagen 11A2 [22], bone morphogenetic protein (BMP)-2 [46], RUNX2 [26], Fibroblast Growth factor 2 [19], BMP-9 [34], TGFB receptor type 2 [17], vitamin K epoxide reductase complex subunit 1 [8], however, the pathogenesis of OPLL remains to be elucidated. The expression analysis of OPLL related genes in Enpp1 mutant mice might be contributory to understanding the pathogenesis of OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…The VKORC1 gene was investigated in 98 OPLL patients and 200 control subjects, with the −1639G> A polymorphism having a significant effect in female patients (OR 5.22, p = 0.004), but not when both sexes were considered together (p > 0.05) [52].…”
Section: Spinal Pathologymentioning
confidence: 99%